Evaluation of Gall Bladder Mucosal Changes in Relation to the Type of Stones in Patients Undergoing Laparoscopic Cholecystectomy: A Retrospective Study of 394 Patients - V. Shirale, Vaishali; Goyal, Sunder; Pujani, Mukta (Journal of Spleen And Liver Research, 2020)
Background and Aim Gallbladder (GB) cancer is a highly fatal malignancy and approx. 10% new cases are diagnosed every year in India. The GB cancer has poor prognosis due to progressive nature. Understanding of risk factors that lead to GB development is urgently required for better management of the disease. Presence of stones in gall bladder generates varied mucosal reactions, which leads to different types of histopathological changes in mucosa. Here, our aim is to study the correlation between various types of mucosal responses e. g. inflammation, hyperplasia, metaplasia and carcinoma with different characteristics e. g. number and morphology of gallstones both in males and females. Materials and Methods A retrospective study of gallstones was performed on 438 cases of cholecystectomies operated laparoscopically based on the histological changes. Out of 438 cases, 394 (89.95%) were associated with gallstones and the rest 44 (10.05%) belonged to acalculous cholecystitis. The mucosal changes in calculous gall bladder were studied in 394 cases and its correlation with number and types of observed gallstones were evaluated. Tissue sections were taken from the fundus, body, neck and abnormal area of gallbladder for histopathological studies. Results Our study has revealed the higher incidence of inflammatory changes in males, while gall bladder hyperplasia, intestinal metaplasia and cancer cases were found mostly in females. Conclusion Our study showed that changes in the number and morphology of gallstones are directly associated with the mucosal changes in gallbladder e.g. inflammation, hyperplasia, metaplasia and gall bladder carcinoma.
Keywords: Cholelithiasis; Gallbladder mucosa; Intestinal metaplasia